Analiza kompetencji rodziców w zakresie bezpieczeństwa dzieci w Internecie - Bartkowiak, Anna (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2012)
In the last three years there had been conducted several researches in Poland, which were related to competences and consciousness of parents in the field of children safety in the Internet, including the research conducted in 2010 in all European Union countries (the EU Kids Online research). In this paper the author focuses mainly on the comparison and synthesis of the result of these researches on safety of children in the Internet and parent’s competences in that matter as well on presentation of conclusions drawn from these results. The paper also presents briefly types and classification of Internet threats, as well the analysis of activities and competences of children in the Web.
An Analysis of Parents’ Competences in Children Safety in the Internet
Keywords: threats in the Internet; children’s safety in the Internet; children in the Web; parents of children in the Web; Internet competences of parents; Internet competences of children